Morphological and pharmacological determinants of peri-procedural myocardial infarction following elective stent implantation: Optical coherence tomography sub-analysis of the PRASFIT-Elective study. Issue 6 (December 2017) - Uzu, Kenzo; Shinke, Toshiro; Otake, Hiromasa; Takaya, Tomofumi; Osue, Tsuyoshi; Iwasaki, Masamichi; Kinutani, Hiroto; Konishi, Akihide; Kuroda, Masaru; Takahashi, Hachidai; Terashita, Daisuke; Hirata, Ken-ichi; et al.
Abstract: Background: Previous studies have suggested that peri-procedural myocardial infarction (PMI) following percutaneous coronary intervention (PCI) is associated with adverse short- and long-term outcomes, and several morphological predictors of PMI have been studied. However, the determinants of PMI under novel anti-platelet therapy are not fully elucidated. Methods and results: PRASFIT-Elective is a multicenter, parallel-group study of PCI patients in non-acute settings receiving either prasugrel or clopidogrel in addition to aspirin. Among 742 study patients, 94 (116 lesions) underwent optical coherence tomography (OCT) to evaluate the area of intra-stent tissue (IST, which comprises tissue protrusion and thrombus) after stenting in addition to standard parameters. We investigated the relationship between the peak creatine kinase (CK)-MB fraction levels after PCI and post-stent OCT findings, as well as on-treatment platelet reactivity determined by the P2Y12 reaction units (PRU) at PCI, in a post hoc manner. The multivariate linear analysis revealed that a larger total IST area (standardized coefficient: 0.370, p  < 0.001) and smaller minimal stent diameter (standardized coefficient: −0.242, p  < 0.014), but not the PRU value ( p  = 0.988), were independently associated with CK-MB leakage. The IST area after stenting was mainly determined by the target lesion lipid index (averaged lipid arc × lipid length) ( r  = 0.583, p  < 0.001). Conclusion: Following elective PCI, a large IST area originating from a lipid-rich plaque and a smaller minimal stent diameter were associated with PMI.